2008
DOI: 10.1111/j.1460-9568.2008.06262.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein degradation, as with protein synthesis, is required during not only long‐term spatial memory consolidation but also reconsolidation

Abstract: The formation of long-term memory requires protein synthesis, particularly during initial memory consolidation. This process also seems to be dependant upon protein degradation, particularly degradation by the ubiquitin-proteasome system. The aim of this study was to investigate the temporal requirement of protein synthesis and degradation during the initial consolidation of allocentric spatial learning. As memory returns to a labile state during reactivation, we also focus on the role of protein synthesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
149
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(158 citation statements)
references
References 40 publications
7
149
2
Order By: Relevance
“…First, we replicated the experiment in the Morris water maze with a simple massed acquisition procedure with reactivation ( Fig. 1C; see Materials and Methods, Experiment 1; Artinian et al 2008) or without reactivation ( Fig. 1E; see Materials and Methods, Experiment 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, we replicated the experiment in the Morris water maze with a simple massed acquisition procedure with reactivation ( Fig. 1C; see Materials and Methods, Experiment 1; Artinian et al 2008) or without reactivation ( Fig. 1E; see Materials and Methods, Experiment 2).…”
Section: Resultsmentioning
confidence: 99%
“…Morris et al (2006) showed that inactivation of the dorsal hippocampus during reconsolidation by anisomycin (a protein synthesis inhibitor) has no effect on the MWM performances. However, in previous studies (Artinian et al 2007(Artinian et al , 2008, we showed that the hippocampal CA3 region is crucial for reconsolidation of spatial information in this same task. Different factors could explain this apparent discrepancy, but the most important fact is that, unlike us, Morris et al (2006) used a distributed learning procedure leading to an asymptotic level of performances before the reactivation trial.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, infusion of the proteasome inhibitor b-lactone into the CA1 region of the hippocampus prevents extinction of contextual fear memory . Also, in using infusion of lactacystin into the CA3 region of the hippocampus it was shown that protein degradation is important for consolidation as well as reconsolidation of spatial memory (Artinian et al 2008). The mechanistic details as to how the UPP contributes to the extinction of fear memory or reconsolidation of spatial memory are not clearly understood.…”
Section: The Upp and Long-term Synaptic Plasticitymentioning
confidence: 99%